Experimental substantiation of modified non-penetrating deep sclerectomy for primary open-angle glaucoma (Ukrainian Journal of Ophthalmology, 2026)
Background: Excessive bleb scarring is the main cause of reduced hypotensive effect after conventional non-penetrating deep sclerectomy (NPDS). We have developed a modification of NPDS with implantation of a drainage device to reduce this scarring.Purpose: To investigate morphologically the inflammatory response and scarring at the operative site after conventional NPDS and modified NPDS (MNPDS) with implantation of different drainage devices in rabbits.Materials and Methods: The animals of Groups I and 3 underwent manipulations similar to conventional NPDS (with implantation of either a 5-0 polyamide thread or Xenoplast drainage device, respectively), whereas those of Groups 2 and 4 underwent manipulations similar to MNPDS (with implantation of either a 5-0 polyamide thread or Xenoplast drainage device, respectively).Results: At week 4, the reparative process in the animals of Group 1 was not yet complete (with insubstantial inflammatory changes still present, mostly around a foreign body), whereas that in the animals of Group 2 was practically complete. In addition, in the animals of Group 3, the process was significantly hindered by active exudative inflammation, whereas in the animals of Group 4, the inflammatory changes were less pronounced.Conclusion: The technique of MNPDS reduces postoperative bleb scarring and results in a shorter reparative process at the filtering site compared to that in conventional NPDS. Extensive dissection of the conjunctiva from the episclera and episcleral diathermocoagulation result in a longer reparative process at the operative site. Incorporation of either type of drainage device (polyamide thread or Xenoplast) into the intrascleral space results in a stable dilatation of the space and prevents the adhesion between the roof and the bed of the scleral tunnel.
Keywords: glaucoma; surgical treatment; non-penetrating deep sclerectomy; morphologic changes at the operative site